Glycine betaine modulates extracellular polymeric substances to enhance microbial salinity tolerance - Yan Xia; Xinbai Jiang; Shuaishuai Guo; Yuxuan Wang; Yang Mu; Jinyou Shen (Environmental Science and Ecotechnology, 2024)
High salinity inhibits microbial activity in the bioremediation of saline wastewater. To alleviate osmotic stress, glycine betaine (GB), an osmoprotectant, is added to enhance the secretion of extracellular polymeric substances (EPS). These EPS are pivotal in withstanding environmental stressors, yet the intricate interplay between GB supplementation and microbial responses through EPS modifications—encompassing composition, molecular architecture, and electrochemical features—remains elusive in hypersaline conditions. Here we show microbial strategies for salinity endurance by investigating the impact of GB on the dynamic alterations of EPS properties. Our findings reveal that GB supplementation at 3.5% salinity elevates the total EPS (T-EPS) content from 12.50 ± 0.05 to 24.58 ± 0.96 mg per g dry cell weight. The observed shift in zeta potential from −28.95 to −6.25 mV at 0% and 3.5% salinity, respectively, with GB treatment, indicates a reduction in electrostatic repulsion and compaction. Notably, the EPS protein secondary structure transition from β-sheet to α-helix, with GB addition, signifies a more compact protein configuration, less susceptible to salinity fluctuations. Electrochemical analyses, including cyclic voltammetry (CV) and differential pulse voltammetry (DPV), reveal GB's role in promoting the release of exogenous electron shuttles, such as flavins and c-type cytochromes (c-Cyts). The enhancement in DPV peak areas (QDPV) with GB addition implies an increase in available extracellular electron transfer sites. This investigation advances our comprehension of microbial adaptation mechanisms to salinity through EPS modifications facilitated by GB in saline habitats.